Surah al-Asr: It’s relevance in a postmodern world - Fontaine, Rodrigue Ancelot Harvey (2019)
This study explores the relevance of surah al-Asr in a postmodern world. Surah al-Asr is a summary of the Qur’an (Khan 1993). Based on Khan’s (1993) reflections, five ontological propositions are derived. The study then explores the evolution of Western philosophy since the 18th century. This includes the birth of the humanist project, Nietzsche’s deconstruction of Western idealism, Heidegger’s reflections on being, and the shift from a modern society to a postmodern society. Postmodernism is a world in which the digital world is more real than reality. Ferry, a French philosopher, summed up the dilemma of Western society by noting that Westerners are desperately in search of a purpose to their lives. All these conflicting philosophies offer profound insights into the second ayah (“Verily, mankind is in a state of loss). The study concludes that surah al-Asr offers profound insights for Muslims and non-Muslims in the 21st century.